87.2k views
4 votes
P - 5(p+4) = p - (8-p)

I need all the steps please but don't show me the new equation in full.

User Atgrubb
by
4.6k points

1 Answer

6 votes

Answer:

Simplifying 6p + 2(4 + -2p) = 3(p + 4) 6p + (4 * 2 + -2p * 2) = 3(p + 4) 6p + (8 + -4p) = 3(p + 4) ... Move all terms containing p to the left, all other terms to the right. ... When you enter an equation into the calculator, the calculator will begin by ... Similarly, 2 * (x + 5) can also be entered as 2(x + 5); 2x * (5) can be entered as 2x(5).

Explanation:

User Alexisdm
by
5.2k points